Experimental and theoretical insight of nonisothermal adsorption kinetics for a single component adsorbent–adsorbate system - Loh, Wai Soong (2013)
A theoretical framework is proposed to describe the temperature-dependent adsorption kinetics and their interpretation of measured uptake curves of four types of adsorbate, namely, methane and halogenated refrigerants (R134a, R410a, and R507a) onto a pitch-based activated carbon, Maxsorb III. The model requires only two measurable data from the experiments, that is, the adsorbent temperature and system pressure during the adsorption dynamics. We have demonstrated that the temperature dependency adsorption has significant influence on the intrapellet diffusion coefficients of the linear driving force (LDF) model. A modified LDF model is proposed in this paper, and it is validated using the uptake behavior of these adsorbates; good agreement is found between the proposed kinetics model and the experimental uptake. The parameters postulated in the model are consistent and reproducible and agree well with a priori estimates. The model provides a useful theoretical basis for the analysis of rapid sorption processes for which the isothermal approximation is no longer valid.